A self-reinforcing and self-healing elastomer with high strength, unprecedented toughness and room-temperature reparability. Issue 1 (17th November 2020) - Li, Yuhan; Li, Wenjuan; Sun, Ailing; Jing, Mengfan; Liu, Xingjiang; Wei, Liuhe; Wu, Kai; Fu, Qiang
Abstract : A mechano-responsive strategy, known as strain-induced crystallization, is proposed to tailor room-temperature self-healing, highly mechanically-strong and unprecedentedly tough polyurethane elastomers. Abstract : The development of intrinsic self-healing elastomers with simultaneous high mechanical strength, toughness and room-temperature reparability remains a formidable challenge. Herein, we report a mechano-responsive strategy, known as strain induced crystallization, to address the above issue, whereby synthesized elastomers with unprecedented high mechanical performances are bestowed with room-temperature self-healing materials, achieving tensile strength, toughness and fracture energy values of 29.0 MPa, 121.8 MJ m −3 and 104.1 kJ m −2, respectively.